Optimal urethral catheter removal time after robotic radical prostatectomy: a systematic review of the current evidence - Mourmouris, Panagiotis; Kostakopoulos, Nikolaos; Argun, Omer Burak; Georgopoulos, Ioannis; Klapsis, Vasillios; Pisiotis, Nikolaos; Salmas, Ioannis; Doganca, Tunkut; Charamoglis, Sotirios (Frontiers in Surgery, 2026)
BackgroundRobotic Radical Prostatectomy has become the dominant surgical approach for localized prostate cancer, offering offers many advantages in postoperative recovery and quality of life. Despite these advances, the standard duration of urethral catheterization- typically 7 days- has remained largely unchanged.ObjectiveTo systematically evaluate the feasibility and safety of early urethral catheter removal after robotic radical prostatectomy and to identify the optimal timing for catheter removal.MethodsA systematic review was conducted according to PRISMA guidelines. PubMed, Web of Science, Cochrane Library, Google Scholar and Scopus databases were searched from inception to August 2025. Case reports, non robotic studies and non English publications were excluded Study quality was assessed using the Newcastle-Ottawa Scale for non randomized studies and the Jadad scale for randomized controlled trials.ResultsThirteen studies involving 4.055 patients met inclusion criteria, including three randomized controlled trials. Early catheter removal was variably defined, most commonly between 1 and 4 post operative days. Across studies early removal was not associated with increased rates of anastomotic leakage, urethral stricture or bladder neck contracture. Continence recovery seams to be occur earlier with early removal although higher short term urinary retention rates were reported. Overall complications and readmission rates were low. Study quality was acceptable despite the limited evidence from high quality randomized studies.ConclusionsEarly catheter removal after robotic radical prostatectomy appears both safe and feasible in appropriate selected patients and may accelerate continence recovery without compromising long-term outcomes. Catheter removal on postoperative days 3-4 appears to offer the most favora.